2021
DOI: 10.1029/2021gl092968
|View full text |Cite
|
Sign up to set email alerts
|

3D Modeling of Long‐Term Slow Slip Events Along the Flat‐Slab Segment in the Guerrero Seismic Gap, Mexico

Abstract: During the last two decades, quasi‐periodic long‐term slow slip events (SSEs) of magnitude up to Mw7.5 have been observed about every 4 years in the Guerrero Seismic Gap, Mexico. We present numerical simulations of the long‐term SSE cycles along the 3D slab geometry of central Mexico. Our model accounts for the hydrated oceanic crust in the framework of rate‐and‐state friction and captures the major source characteristics of the long‐term SSEs occurring between 2001 and 2014, as inferred from geodetic observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Liu and Rice (2007) showed that the fault response transitions from decaying oscillations to seismic events with increasing W/h*, with slow slip emerging in between the two. Likewise, previous models of SSEs in 2D (Liu & Rice, 2009) and 3D non-planar faults (Li & Liu, 2016;Perez-Silva et al, 2021) pointed out that the source properties of SSEs (e.g., slip rate, recurrence interval and magnitude) tend to positively correlate with changes in W/h*.…”
Section: Effect Of Spatial Variations In the Effective Fault Stiffness Ratio W/h* On Sse Properties And Fault Slip Behaviormentioning
confidence: 77%
See 1 more Smart Citation
“…Liu and Rice (2007) showed that the fault response transitions from decaying oscillations to seismic events with increasing W/h*, with slow slip emerging in between the two. Likewise, previous models of SSEs in 2D (Liu & Rice, 2009) and 3D non-planar faults (Li & Liu, 2016;Perez-Silva et al, 2021) pointed out that the source properties of SSEs (e.g., slip rate, recurrence interval and magnitude) tend to positively correlate with changes in W/h*.…”
Section: Effect Of Spatial Variations In the Effective Fault Stiffness Ratio W/h* On Sse Properties And Fault Slip Behaviormentioning
confidence: 77%
“…Given that the smallest value of the critical nucleation size ( h *) is 80 km, h */ dx ∼80, where dx is the average length of the triangle edges (1 km). Such discretization ensures that h * is well resolved, and is similar to that used in previous 3D simulations of SSEs (Li et al., 2018 ; Li & Liu, 2016 , 2017 ; Perez‐Silva et al., 2021 ). We note that our model neglects normal stress changes induced by slip on the non‐planar fault, similar to previous SSE models in non‐planar faults (e.g., Li & Liu, 2016 ; Shibazaki et al., 2012, 2019 ).…”
Section: Model Setupmentioning
confidence: 87%
“…However, it is interesting to note that conditions of relatively homogeneous τn ${\tau }_{n}^{\prime }$ and shear strength may actually emphasize the influence of geometry on earthquake behavior, as geometry becomes the main control on shear strength variation along the megathrust. Both effects may be explored in future work focusing on variations in megathrust geometric complexity and cycles of fault slip (e.g., Perez‐Silva et al., 2021) and by relaxing our assumption of a constant shear to effective normal traction ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Within the rate‐and‐state friction (RSF) framework (Dieterich, 1979), SSEs commonly require rate‐weakening friction to nucleate, while different mechanisms (e.g., transition to rate‐strengthening friction at higher slip speeds, Shibazaki, 2003; dilatancy strengthening, Segall et al., 2010; transitional friction behavior, Liu & Rice, 2007) have been proposed to stabilize the growing unstable slip. These models, although successful in reproducing SSE characteristics (e.g., Dal Zilio et al., 2020; Li & Liu, 2016; Liu & Rice, 2009; Matsuzawa et al., 2013; Perez‐Silva et al., 2021, 2022; Shibazaki et al., 2012, 2019), do not account for the temporal variation in pore pressure nor the widespread occurrence of rate‐strengthening materials in slow slip regions (e.g., Bürgmann, 2018; Ikari et al., 2013; Saffer & Wallace, 2015). An alternative modeling approach, proposed by Perfettini and Ampuero (2008), suggests that transient slip is induced in rate‐strengthening conditions by external stress perturbations.…”
Section: Introductionmentioning
confidence: 99%